PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI SISWA SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted to enhance the poetry writing skills of the fourth-grade students at SD. IT Hamalatul Ilmi Bangkinang through the implementation of the Contextual Teaching and Learning model. The research used a classroom action A mixed-methods research approach is conducted in two successive cycles, each with its phase of planning, implementation, observation, and reflection stages. The research subjects consisted of seven students. Data collection occurred through observation, writing poetry tests, interviews, and documentation, and were analyzed using descriptive qualitative and quantitative approach. The findings point out that the application of the The CTL model improved student performance in writing poetry in terms of diction, theme, and This means meaning, poetic structure, as well as imagination and creativity. The CTL model is effective in teaching the writing of poetry in primary schools.